Improving The Ability Of Writing One-Chapter Drama Text With The Picture And Picture Learning Model Of VIII Class Students SMP Negeri 1 Amandraya - Gokli Sinaga; Yusni Khairul Amri; Titi Lestari (Indonesian Journal of Education and Mathematical Science, 2021)
This study aims to determine whether there is an increase in the Picture and Picture learning model on the students' ability to write one-act drama scripts in class VIII SMP Negeri 1 Amandraya.This type of research is a classroom action research with research subjects, students of class VIII-2 SMP Negeri 1 Amandraya, totaling 32 people. The object of this research is the student learning outcomes in writing a one-act drama script. The I and II learning outcomes tests are in the form of products. In testing the hypothesis classical completeness is used, namely the number of students who meet or more than the minimum KKM is 75%.The results of the research cycle I the average value of students 72.81 with 10 students or 34% complete. The lowest score in the first cycle was 60 and the highest score was 83. Furthermore, in the second cycle the students' average score increased to 79.5 with 93.75% completeness or 30 students. The lowest value in the second cycle was 72 and the highest value was 88. The results of the calculation were that classical completeness in the second cycle was greater than the minimum classical completeness, namely 93.75%> 75%. It can be concluded that the application of the picture and picture learning model can improve student learning outcomes in writing drama scripts